The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1136/archdischild-2017-314367
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of infant heart rate assessment by auscultation, ECG and oximetry in the delivery room

Abstract: Clinical assessment of an infant's heart rate (HR) in the delivery room (DR) has been reported to be inaccurate. We compared auscultation of the HR using a stethoscope with electrocardiography (ECG) and pulse oximetry (PO) for determining the HR in 92 low-risk newborn infants in the DR. Caregivers auscultated the HR while masked to the HR on the monitor. Auscultation underestimated ECG HR (mean difference (95% CI) by -9 (-15 to -2) beats per minute (bpm)) and PO HR (mean difference (95% CI) by -5 (-12 to 2) bp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 8 publications
1
17
0
2
Order By: Relevance
“…Additionally, Murphy et al determined auscultation and PO underestimated ECG HR by a mean difference (95% confidence interval) of −9 (−15 to −2) and −5 (−12 to 2) bpm, respectively [23]. This supports previous studies, which identified the other techniques underestimate ECG HR for infants with HR >100 bpm.…”
Section: Electrocardiographysupporting
confidence: 61%
See 3 more Smart Citations
“…Additionally, Murphy et al determined auscultation and PO underestimated ECG HR by a mean difference (95% confidence interval) of −9 (−15 to −2) and −5 (−12 to 2) bpm, respectively [23]. This supports previous studies, which identified the other techniques underestimate ECG HR for infants with HR >100 bpm.…”
Section: Electrocardiographysupporting
confidence: 61%
“…Accounting for placement, pulse detection, listening window of 6 s, and time required for mental computation, this technique allows for quick approximation of HR. A total HR assessment time ranging from 7-19 s on average have been previously reported for both palpation and auscultation [16,23,24].…”
Section: Auscultation/palpationmentioning
confidence: 99%
See 2 more Smart Citations
“…All tests were two sided and a p value <0.05 was considered statistically significant. Statistical analysis was performed using R V.3.3.0 (R Foundation for Statistical Computing, Vienna, Austria) 14…”
Section: Methodsmentioning
confidence: 99%